VIBRATION ANALYSIS OF SHIP MAIN ENGINE AND SHAFT SYSTEM - Alarcin, Fuat; Korkmaz, Fatih Cuneyd (YILDIZ TECHNICAL UNIV, 2012)
Ship is driven by machine power and various of dimensions of electrical and mechanical structures As it is possible to see vibration on each machine, it can be seen on ship mechanical system as well. The goal of this paper is to decrease of vibration oscillations on ship main engine shaft system. The mathematics model of system is composed by Lagrange method and also the effect of dynamics forces which are consisted of main engine streses and the hydrodynamic forces which come from water effect are also taken into consideration. The axial and torsional vibration were the factors during the analyse. Matlab - Simulink is used to obtain the oscillation of axial and torsional vibrations and to make these oscillations less different types of damping coefficiency effects are investigated.
Keywords: Ship main engine propulsion systems; vibrationanalysis; analysis of frequencies; torsional; Engineering